The importance of wilderness landscape Analysis in development planning schemes for national parks, with special reference to the Mountain Zebra National Park - W. van Riet (Koedoe: African Protected Area Conservation and Science, 1977)
Definition of the Concept "Wilderness" The Wilderness Act of September 1964, of the United States of America, states that "... wilderness, in contrast with those areas where man and his own works dominate the landscape, is hereby recognised as an area where the earth and its community of life are not influenced by man and where man himself is a visitor who does not remain55 (Nash 1967). The Act also states that a wilderness "... must retain its primeval character and influence and that it must be protected and managed in such a way that it appears to have been effected primarily by the forces of nature.”